PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJARMATEMATIKASISWA KELAS IV SD NEGERI 9 TENGGAYUN KECAMATAN BUKIT BATU - Tuti Asnita; Eddy Noviana; Syahrilfuddin Syahrilfuddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is motivated to learn math low students at fourth grade SD Negeri 9 Tenggayun. The population is 33 students with KKM 65 only 12 (36,36%) students pass to KKM, but 21 (63,64%) students under to KKM. The average of math is 63,21. From the problem above the research we the act of class research (PTK) with the appicate of cooperative learning NHT type. Students result increase from average first data is 63,21 to UH I is 69,09 to 9,30%, but UH II is 80 to 15,7%. Persentase for teacher activities, first cycles for first meet is 66,6% with category is enough, for second meet is 70,8% with category good. Second cycles for first meet is 79,1% with category good and for second category is 87,5% with category is very good. The students activities for cycles 1 for first meet is 62,5% with category is enough. For second meet is 66,6% with category is enough. Sycles II for first meet is 75% with category good and for second meet is 83,3% with category is very good. The classical value for cycles I and II get it. The application of cooperative learning NHT type can increase the students result in math for fouth grade SD Negeri 9 Tenggayun Kecamatan Bukit Batu.Key word: Coopetative NHT Type, Result Of Math